The Role of the Integrated Financial Adviser in the Government of India - World Bank (Washington, DC, 2014)
The research paper compares the various thoughts and models of the finance function in the Indian Central Government with those that exist worldwide, presents the analytical underpinnings of why some aspects of a particular model may be suitable to the Indian position, and provides the Government of India with options and courses of action. The paper offers historical and current perspective (chapters two and three) on the development of the role of Financial Adviser (FA), comparative lessons from other countries on how they have structured this position (chapter four), suggestions on appropriate training and certification programmes for financial advisers and their key support staff and opportunities for commensurate career development that makes the FA position more attractive for Government of India (GoI) officers and talented applicants (chapters five and six).